2021
DOI: 10.16984/saufenbilder.796745
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Effects on Fatigue Behavior of Zn-Cr+3 and Zn Flake Coated M8 DIN 933 Bolts

Abstract: In this study, fatigue behavior of Zn-Cr+3 and zinc flake coated bolts was investigated experimentally by considering corrosion effects. Fatigue tests were conducted on M8x50x1.25 8.8 DIN 933 bolts at normal and corroded conditions at force amplitudes between 2.35 and 5.36 kN at test frequency of 75 Hz. A part of bolts was subjected to salt atmosphere for corrosion. According to the Wöhler curves obtained from fatigue tests before corrosion, zinc flake coated bolts showed 1.55 times higher fatigue life compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Research has shown that the stress intensity factor K 1 is a significant indicator characterizing the stress corrosion process in metals [ 33 ]. Corrosion cracking can typically cause ductile metal alloys subjected to high temperature and tensile stress to fail suddenly [ 34 ].…”
Section: Harsh Environmental Conditions That Exacerbate Sccmentioning
confidence: 99%
“…Research has shown that the stress intensity factor K 1 is a significant indicator characterizing the stress corrosion process in metals [ 33 ]. Corrosion cracking can typically cause ductile metal alloys subjected to high temperature and tensile stress to fail suddenly [ 34 ].…”
Section: Harsh Environmental Conditions That Exacerbate Sccmentioning
confidence: 99%
“…It is ideal for components for which the standards require high demands on accuracy of fit without rework, like bolts and nuts. [ 1,9 ]…”
Section: Introductionmentioning
confidence: 99%